Dicotyledonous wood from the Upper Cretaceous (Maastrichtian) of Coahuila - Sergio R.S. Cevallos-Ferriz; Reinhard Weber (Revista Mexicana de Ciencias Geológicas)
A silicified Wood collected from Maastrichtian sediments of the Olmos Formation, near Agujitas, State of Coahuila, has anatomical characteristics similar to those from the wood of the phyllantoid group (Euphorbiaceae)… in order to continue, download the full paper in PDF.